Fuelwood Consumption Pattern of Van-Gujjars Vis-a-Vis Adjoining Villages of Kalagarh and Lansdown Forest Division, Uttarakhand - Chander Shekhar; Negi, A. K.; Gopal, Ram (Indian Forester, 2019)
The present study was carried out in 2013 to understand the fuelwood consumption pattern by Van Gujjars and adjacent villagers in and Kalagarh and Lansdown Forest Division, Uttarakhand. A total of twenty four settlements of Van Gujjars and fifteen settlements of adjacent villages were surveyed. Overall average fuelwood consumption in context to family size and income group was higher in Van Gujjars community compared to adjacent villagers. During that time, lack of communication, high prices of alternative source of energy, poor financial condition were the key factors for dependency on forest for fuel and fodder.